Markdown & vous L'écriture académique au format texte avec Markdown et Pandoc - Pochet, Bernard (Presses universitaires de Liège, 2023)
With digital technology and what it can offer us but also what it tends to impose on us, it becomes necessary to stop for a moment. This manual is dedicated to academic writing with Markdown and Pandoc. It is both a plea for open digital writing and an introduction to Markdown and Pandoc, and offers a reflection on our tools and methods of academic writing. It is not, however, limited to beginners. The idea is to go back to the basics and not to try to reproduce at all costs everything that is possible with a classic word processor (which we can do without). The aim of this manual is to explain why it is possible to change one's habits in order to write, structure one's ideas and produce quality documents, and to show what is possible with Markdown through a few methods.